The Prevalence of Thrice, Twice, and Once Human Papillomavirus DNA Positivity in Older Chinese Women - Hu, Guomin; Xu, Jun; Xu, Ling; Jin, Longmei (Frontiers in Medicine, 2020)
Background Human papillomavirus (HPV) DNA detection in cervical samples is widely used to identify HPV infection; however, the characteristics of HPV prevalence evaluated by repeated DNA detection in community populations are still vague. Methods Beginning in 2014, a Papanicolaou (Pap) smear and HPV cotesting program was implemented among older women living in the Minhang district of Shanghai. Of 225,000 person-time data, 632 subjects who had 3 repeated visits and at least one HPV DNA-positive result in the last 5 years were involved in this report. Results All 16 genotypes of HPV displayed thrice, twice and once positivity results in 3 repeated tests and differed by proportions among and within genotypes. HPV52 and 58 are the top two genotypes dominant in total and thrice positive person-time. The thrice positive person-time exceeded 50% in each of HPV58-, 35-, 52-, 56-, 18-, 68-, 31- and 16-infected women. The single positive person-time ratio ranged from 7.9% (HPV35) to 38.9% (HPV11). Age differed among and within genotypes in thrice, twice and once positive women. The average age of HPV-free controls was 59.0 ± 7.2 yo, which is close to the median of average ages for thrice and twice positive women and is older than most average ages for once positive women. The percentages of negative for intraepithelial lesion or malignancy (NILM) for thrice HPV52-, 58-, 16-, 56- and 59-positive women were significantly lower than the percentage of NILM for HPV-free women. Conclusion Thrice and/or twice HPV DNA positivity are common in HPV-infected women and tend to occur in older women.